Technical report: the harvesting of Red Tilapia by using logistic growth model / Aliff Rhuzainie Mohd Ghani, Muhammad Irfan Ahmad and Mohammad 'Irfan Ismail - Mohd Ghani, Aliff Rhuzainie; Ahmad, Muhammad Irfan; Ismail, Mohammad 'Irfan (2016)
Tilapia is the common name for almost hundred species of cichlid fish from the tilapiine cichlid tribe. Tilapia is less commonly found living in brackish water but they are mainly freshwater fish inhabiting shallow streams, ponds, rivers and lakes. Red Tilapia or it's scientific name "Oreochromis Niloticus" is the second most farmed fish species in worldwide. It's broad tolerance to an array of environment becomes an important model for studies of fish physiology. A red tilapia started to appear in the aquaculture industry back in the mid-1980s. Red Tilapia has become a popular type of Tilapia in Malaysia. A canvas for reinvested earnings and lucrative returns are provided from the preferred fish and a favourite by breeders of freshwater fish ponds, animal in a cage and the system. Consumer acceptance upon continued high demand come due to the ability of red tilapia to grow quickly as well as to multiply quickly, easier to manage and having less disease. Consequently, farming tilapia has given lots of benefits. From all information we had, this project used Logistic Growth Model with no, constant and proportional harvesting to estimate the population of tilapia. This model is used to represent the population of tilapias with and without harvesting. In this research, we are trying to compare the method of harvesting such that logistic growth model without harvesting, logistic growth model with constant harvesting, and logistic growth model with proportional harvesting. From the result, we can identify that the best method to harvest is by using logistic growth model with proportional harvesting.